Eating Habits Among School Students - Syakir, Muhammad Syazwan; Kamal, Azlan Ahmad; Rahman, Zarizi Ab (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
In this study, schoolchildren's eating behaviors are examined. The purpose of this study is to determine how habits affect student development and how eating patterns affect bmi in the classroom. This study used a quantitative methodology that relied on questionnaires. Google Forms was used to build the survey. 500 respondents representing the population of the study are kids from grades 1 through 5 at SMK Seksyen 18. The study's findings indicate that students' eating habits and BMI have a substantial impact on them.